THE DYNAMICS OF ANTIMICROBIAL RESISTANCE OF Salmonella typhimurium ISOLATES. - Erleta Peqini; Zheni Brahimaj; Sotir Mali; Klementina Puto; Ariola Devolli; Naxhije Hila; Aida Dervishi (Peytchinski Publishing, 2011)
Salmonella typhimurium is the most common pathogen isolated in foodstuffs toxin infections. The development of antibiotic resistance in Salmonella typhimurium over the last twenty years is caused by an extensive application of some antibiotics. The study of antimicrobial resistance of Salmonella typhimurium isolates helps the physicians in using the indispensable antibiotic and replacing the resistant antibiotics with new ones. The aim of this study was to determine the prevalence of antimicrobial resistance of Salmonella typhimurium isolates of persons with foodstuff's toxin infections in Elbasan region during the years 1985-2004, to which are made the antibiograms and the antimicrobial resistance. This study includes 2931 Salmonella typhimurium strains in this period of time. All the strains were tested using disk diffusion method (with antibiotics: AM, S, TE, C, K, GM, SXT, NA and CIP). Salmonella typhimurium strains have been more resistant to Ampicilin (98.29 %), Tetracycline (93.48 %, Streptomycin (78.92 %), Bactrim (64.14 %).The reason of passivity of such antibiotics against Salmonella typhimurium is their use, in most cases, without doing the antibiograms in each case and physicians have used very often the above antibiotics, bringing about the intensification of bacteria's resistance towards them.